(3Gdhaj aj LeY CMGOjK GdcJH GdCQHYI GdbOjeIs - (3GdcGTj, ajVj, eMSf Hf eMeO Hf eQJVi GdcGTj GdTjYj, J (B1091(3g` (B1680(3es
(3ChdgG (B:s
(3ChdgG(B: (3fMeOc Gddge jG ef gOGfG HCfhGQ GdbQBf hGdMOjK deYQaI GdaQGFV (B... (3gPG jG ENhGfj cJGH hGa aj afhf Ydhe GdOjf jMJhj Ydi LedI eG hQO aj GdbQBf GdeHjf hLejY eG JVefJg CUhdfG GdCQHYI GdJj YdjgG GdeOGQs
(3BNQgG (B:s
(3BNQgG(B: (3hHbhdg JYGdi Mjf ef GdOgQ eG HYO Ndb GdSehGJ hGdCQVjf hJbOjQGJ GdCTjGA hJOHjQgG hdgPG bGd dc jcf TjFG (B.. (3hGdePchQ eG MUd aj GdPcQ Cj aj GdMGVQ (B. (3BNQ CHhGH eYQaI eNdhbGJg hCaYGdgs
(3JHUQI GdeDda (B:s
(3aj GdPQjYI(B: (3eMeO Hf eQJVis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 22s
(3GdPQjYI, L (B25: 11s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs